Picketing Marriott's Great America - Sahl, Ted (photographer):::Creator::::::::::::
Lambda Association and their supporters picket Marriott's Great America theme park and the Great Outdoor Association. Picketers hold signs that read, "G.O.A. Go...Away" and "Spend gay money...we lose gay rights".